SISTEM INFORMASI PEMASARAN RUMAH DI GRAHA PERMATA SURYA MIJEN SEMARANG BERBASIS WEB (Information Technology and Telematics, 2015)
Abstract : At this present moment in life as well as increasing competition in the business, it brings a huge impact on people's demands for services and information fast, accurate, safe and comfortable in which society as a businessman and as a customer. Similarly, in the trading business, services such as the above plays an important role. Utilizing the web is one of the alternative ways to improve the service. By using the Web no longer limitations of space and time to obtain the required information as quickly as over the internet. This study aims to facilitate the prospective consumers in obtaining housing information quickly, easily and efficiently and build a marketing strategy to the public housing through the web. This new web-based system to perform payment transactions made by means of transfers between bank accounts via ATM or through a cash deposit to the account number PT. Bagoes Property. After payment, the consumer is expected to confirm the payment order into the system in order to be displayed into the financial statements that can be viewed by the owner of PT. Bagoes Property.   Keywords: sisfo, pemasaran rumah, graha permata surya, mijen